Do transnational links matter after return? Labour market participation among Ghanaian return migrants - Setrana, Mary Boatemaa (2014)
Previous studies on transnationalism have looked at ‘remittances’ and ‘short-term visits’ to the home community and its transformational impact. However, little attention has been given to how transnational links enable return migrants to economically reintegrate into the home community. Although transnationalism describes return migration as a circular movement, there is still evidence of permanent return. Using Ghana as an example, this paper examines the conditions, strategies, assets and labour participation of return migrants. The study employed both qualitative and quantitative methods in investigating its set objectives. The study found that for wage employed returnees, maintaining professional contacts abroad is a key factor in ensuring their sustenance in the local and global job market. On the other hand, having investments abroad is important for self-employed returnees to sustain their return. The paper suggests that in order to promote national development and enhance national competitiveness in a globalizing world, Ghana needs to strengthen both its educational and business sectors. With this goal in mind, Ghana needs to encourage collaboration amongst its residents abroad and encourage opportunities for the sharing of knowledge and expertise.